A new minimally invasive guided endodontic microsurgery by cone beam computed tomography and 3-dimensional printing technology - Jong-Eun Kim; June-Sung Shim; Yooseok Shin (Restorative Dentistry & Endodontics)
Endodontic microsurgery is defined as the treatment performed on the root apices of an infected tooth, which was unresolved with conventional root canal therapy. Recently, the advanced technology in 3-dimensional model reconstruction based on computed tomography such as cone beam computed tomography has opened a new avenue in application of personalized, accurate diagnosis and has been increasingly used in the field of dentistry. Nevertheless, direct intra-oral localization of root apex based on the 3-dimensional information is extremely difficult and significant amount of bone removal is inevitable when freehand surgical procedure was employed. Moreover, gingival flap and alveolar bone fenestration are usually required, which leads to prolonged time of surgery, thereby increasing the chance of trauma as well as the risk of infection. The purpose of this case report is to present endodontic microsurgery using the guide template that can accurately target the position of apex for the treatment of an anterior tooth with calcified canal which was untreatable with conventional root canal therapy and unable to track the position of the apex due to the absence of fistula.